Linear solution of the passive localization problem with combined single-station direction finding and two-station time difference information - Yu, Tao (BOHR Journal of Computational Intelligence and Communication Network, 2024)
Based on the main station’s direction measurement value and the time difference measurement value of the two stations, two definite solution equations can be listed in the polar coordinate system by directly utilizing the path difference equation and the cosine theorem, and the analytical solution can be obtained by solving the two definite solution equations jointly. Further comparison of the ranging errors shows that the ranging accuracy of the two-station directional and time-difference positioning system is only slightly worse than that of the three-station time-difference positioning system. The new results provide a better basis for the engineering design of two-station hybrid localization.